Perbedaan Stres Persiapan Hari Raya Galungan pada Ibu Rumah Tangga dan Ibu Bekerja yang Beragama Hindu di Denpasar - Hantosa, Bagus Galih; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2013)
Galungan is Hindu religious holy day in celebrating the triumph of dharma over adharma. In Galungan preparation, the mothers, housewives and working mothers, are the one who in charge to prepare all banten that needed on Galungan. Preparing Galungan’s banten was not an easy task because skill, knowledge and time are needed to prepare all the banten, that why this activity had potential to make stress among housewives and working mothers. This study aimed to discover the difference Galungan preparation’s stress between Hindus housewives and working mothers in Denpasar   Sampling technique used in this research was simple random samplings that were 100 subjects consisting of 52 working and mothers and 48 housewives that lived in Denpasar area, that filled the scale of Galungan Preparation’s Stress that was made by stress aspect from pyshic, emotional, and concentration by Dr. Robert J. an Amberg, Cary Cooper, Alison Straw and Braham. From available 60 items, 55 items was declared dan 5 items fall with reliability value 0,974,. Method of analyzing data used in this research is the analysis of parametric t-test independet group. Results from test data analysis is that there is a significant value of p= 0.000 which indicates a significant stress difference between both group of Hindus housewives and working mothers, which was working mothers have more stress level than housewives when working on Galungan’s preparation.   Keywords : Galungan, Stress, Working Mothers, Housewives